AI-Driven Computational Frameworks: Advancing Edge Intelligence and Smart Systems - G. Prabaharan; S. Vidhya; T. Chithrakumar; K. Sika; M.Balakrishnan (International Journal of Computational and Experimental Science and Engineering, 2025)
The rapid advancements in Artificial Intelligence (AI) and Edge Computing are transforming modern computing paradigms by enabling real-time processing, low-latency decision-making, and enhanced intelligence in smart systems. This paper presents an AI-driven computational framework that integrates Edge Intelligence (EI) with adaptive deep learning models to optimize data processing and decision-making at the edge. The proposed framework employs federated learning, neuromorphic computing, and reinforcement learning-based optimization to improve efficiency, security, and scalability in distributed edge environments. Key components include lightweight AI models for energy-efficient edge inference, privacy-preserving techniques using homomorphic encryption and blockchain, and self-learning architectures for adaptive real-time analytics. The study evaluates the framework’s performance in diverse applications, including smart healthcare, autonomous vehicles, and industrial IoT, demonstrating significant improvements in computational efficiency, network resilience, and response time compared to traditional cloud-based architectures. Comprehensive simulations and real-world case studies validate the feasibility and effectiveness of the proposed approach, showing a 35% reduction in latency, a 30% increase in energy efficiency, and a 50% improvement in decision accuracy in edge-enabled smart systems. This research highlights the critical role of AI-driven computational frameworks in advancing next-generation intelligent computing, paving the way for autonomous, secure, and efficient edge-based smart environments.